Culturas juvenis, mídias e consumo: mediações em educação / Youth culture, media and consumption: educational interventions - Maria do Carmo Alves do Bomfim; Luzineide dos Santos Conceição (Universidade Estadual de Campinas, 2010)
Estudos recentes têm enfocado a cultura juvenil, entretanto há lacunas quanto aos desejos dos jovens. O presente estudo registra resultados de pesquisas do Observatório de Juventudes, Cultura de Paz e Violências na Escola - OBJUVE da Universidade Federal do Piauí, especificamente sobre as práticas dos grupos de Hip Hop Vida na Periferia "Vida P" e Movimento pela Paz na Periferia "MP 3" e outra pesquisa sobre "Juventudes, Mídias e Violências", objetivando compreender as mediações formativas na construção das identidades das/os jovens envolvidas/os em práticas em tais práticas de sociabilidades. São referências teóricas desse trabalho os estudos de Adad (2004), Fischer (2008), Catani e Gilioli (2008), Bomfim (2006), Sposito (2003) dentre outras, que foi operacionalizado por meio de observação nos espaços onde se encontravam os sujeitos dessas pesquisas e de aplicação de questionário com perguntas abertas e fechadas. Como resultados podemos registrar que as identidades dos/as jovens da periferia de Teresina são construídas em meio a grupos de amigos, dos movimentos de que participam e de colegas do espaço escolar através de atividades culturais específicas (cine-periferia, teatro, danças etc.) mediadas por ações formativas planejadas. Não obstante essa formação, os/as jovens sofrem forte influência de atrativos para consumo mercadológico via instituições midiáticas, além de reforçarem práticas de violência. This article deals with the modus operandi of the egressed students of higher education, native from the rural area, with work experience in their childhood and that had access to the best courses at Vale do Acaraú University, Sobral, Ceará. The discussed autobiographical research was relevant bearing in mind that, in their life history, the personal and familiar strategies preponderated over the context of poverty, subsistence, since the childhood during the primary school teaching, the adolescence in the middle school, until the youth in the university. The main strategies verified in their narratives are related to the social capital (interpersonal relationships), the knowledge and values transmitted by the family. We can verify the urgency of public policies of inclusion in the higher education in order to suit a considerable demand of people that doesn't have access to higher education, or have access, and with difficulty, continue studying and graduate, specially at UVA (Vale do Acaraú University) that, being a state university, doesn't apply the new "democratic" policies of teaching in higher education, such as ENEM and PROUNI. The results of the research can be applied both micro and macro scopes. The micro area of the classroom can suffer a strong influence in the teaching- learning process when It is known the school strategies of the students. The central administration of the university can also benefit from this study for an institutional evaluation, aiming the strategic planning of administrative instances, such as pro-rectorship for graduation, student subjects, scientific initiation and research.